Kemitraan Pemerintah Daerah dan Efektivitas Pelayanan Publik - Mahmudi Mahmudi (Universitas Islam Indonesia, 2007)
Local government partnership is one of the strategic issues that recently adopted vastly by developed countries as well as developing countries. The trend of outsourcing or contracting out several public services to private sector or third sector increases in recent decade. As a part of the New Public Management doctrine, local government partnership is another form of market oriented in providing public service in order to make better service, efficiency and effectiveness (value for money). There are many schemes for local government partnership that each of them contain potential benefits and risks or losses, so special assessment, well designed and planning is needed by government official before making decision. Keywords: kemitraan, pelayanan publik, efisiensi, dan efektivitas